Codewar: interpretasi terhadap asas pengaturcaraan - Hamid, Erman (Penerbit UTeM Press, 2023)
Codewar: Interpretation of the Basics of Programming is a manuscript published for the first time, showcasing the programming knowledge and talent among Malaysian students. The project, organized by FTMK at Universiti Teknikal Malaysia Melaka, aims to promote STEM and encourage participation in the next edition of Codewar. The manuscript aims to provide an overview of the 2021 participants' writings.